Urinary Klotho measured by ELISA as an early biomarker of acute kidney injury in patients after cardiac surgery or coronary angiography - Isidro Torregrosa; Carmina Montoliu; Amparo Urios; Carla Giménez-Garzó; Patricia Tomás; Miguel Ángel Solís; Carmen Ramos; Isabel Juan; María Jesús Puchades; Guillermo Sáez; María Luisa Blasco; Alfonso Miguel (Nefrología (English Edition), 2015)
Background: Acute kidney injury (AKI) is a common complication after cardiac surgery and percutaneous coronary interventions which markedly worsens prognosis. In recent years, new early biomarkers of AKI have been identified, but many important aspects still remain to be solved. Klotho is a pleiotropic protein that acts as a paracrine and endocrine factor in multiple organs. Reduced renal Klotho levels have been show in several animal models of AKI. No study has been published in which Klotho was tested in humans as an early marker of AKI. The aim of this work is to assess the usefulness of measuring urinary Klotho for the early diagnosis of AKI in patients with acute coronary syndrome or heart failure undergoing cardiac surgery or coronary angiography. Methods. Urinary Klotho was measured 12 hours after intervention in 60 patients admitted to the Intensive Care Unit with acute coronary syndrome or heart failure secondary to coronary or valvular conditions, who underwent coronary angiography (30 patients) or cardiac bypass surgery or heart valve replacement (30 patients). The primary endpoint used was the onset of AKI according to the RIFLE classification system. Human Klotho levels were measured using an ELISA assay. Results: We found no differences in urinary Klotho levels between AKI patients and those who did not develop AKI. Moreover, there was not significant correlation between urinary Klotho levels and the presence of AKI. Conclusion. Urinary Klotho measured by ELISA does not seem to be a good candidate to be used as an early biomarker of AKI.